Corporate Social Responsibility and Firm Size on Earnings Management: Financial Profitability as Mediating Variable - Sunda Ariana; Setyani Dwi Lestari; Suharno Pawirosumarto; Yuwono Yuwono; Sundari Soekotjo (Pusat Penerbitan dan Publikasi Ilmiah, FEB, Universitas Muslim Indonesia, 2022)
This study examines and determines the effect of corporate social responsibility disclosure and firm size on earnings management with profitability as an intervening variable in banking companies listed on the Indonesia Stock Exchange. The population in this study are banking companies listed on the Indonesia Stock Exchange for the 2019-2021 period, a total of 43 banking companies. The sampling technique used in this study used purposive sampling, so the research data obtained were 11 banks. The data source used in this study is secondary data in the form of annual financial statements of banking companies listed on the Indonesia Stock Exchange (IDX) for 2019-2021. The analytical method consists of descriptive statistical analysis, classical assumption test (normality test, multicollinearity test, heteroscedasticity test) and testing all hypotheses through multiple linear regression analysis, path analysis, t-test and coefficient of determination test. The results show that CSR disclosure has a positive and insignificant effect on earnings management in banking companies listed on the Indonesia Stock Exchange. Firm size negatively and significantly impacts earnings management in banking companies listed on the Indonesia Stock Exchange. Profitability positively and substantially affects earnings management in banking companies listed on the Indonesia Stock Exchange. CSR disclosure has a positive and insignificant impact on banking companies' profitability on the Indonesia Stock Exchange. Firm size positively and significantly affects profitability in banking companies listed on the Indonesia Stock Exchange. Profitability cannot influence CSR disclosure and company size on earnings management in banking companies listed on the Indonesia Stock Exchange.